Efficacy and safety of artemether–lumefantrine, artesunate–amodiaquine, and dihydroartemisinin–piperaquine for the treatment of uncomplicated Plasmodium falciparum malaria in three provinces in Angola, 2017 - Davlantes, Elizabeth (Malar J, 2018)
BACKGROUND: The Angolan government recommends three artemisinin-based combinations for the treatment of uncomplicated Plasmodium falciparum malaria: artemether–lumefantrine (AL), artesunate–amodiaquine (ASAQ), and dihydroartemisinin–piperaquine (DP). Due to the threat of emerging anti-malarial drug resistance, it is important to periodically monitor the efficacy of artemisinin-based combination therapy (ACT). This study evaluated these medications’ therapeutic efficacy in Benguela, Lunda Sul, and Zaire Provinces. METHODS: Enrollment occurred between March and July 2017. Study participants were children with P. falciparum monoinfection from each provincial capital. Participants received a 3-day course of a quality-assured artemisinin-based combination and were monitored for 28 (AL and ASAQ arms) or 42 days (DP arm). Each ACT was assessed in two provinces. The primary study endpoints were: (1) follow-up without complications and (2) failure to respond to treatment or development of recurrent P. falciparum infection. Parasites from each patient experiencing recurrent infection were genotyped to differentiate new infection from recrudescence of persistent parasitaemia. These parasites were also analysed for molecular markers associated with ACT resistance. RESULTS: Of 608 children enrolled in the study, 540 (89%) reached a primary study endpoint. Parasitaemia was cleared within 3 days of medication administration in all participants, and no early treatment failures were observed. After exclusion of reinfections, the corrected efficacy of AL was 96% (91–100%, 95% confidence interval) in Zaire and 97% (93–100%) in Lunda Sul. The corrected efficacy of ASAQ was 100% (97–100%) in Benguela and 93% (88–99%) in Zaire. The corrected efficacy of DP was 100% (96–100%) in Benguela and 100% in Lunda Sul. No mutations associated with artemisinin resistance were identified in the pfk13 gene in the 38 cases of recurrent P. falciparum infection. All 33 treatment failures in the AL and ASAQ arms carried pfmdr1 or pfcrt mutations associated with lumefantrine and amodiaquine resistance, respectively, on day of failure. CONCLUSIONS: AL, ASAQ, and DP continue to be efficacious against P. falciparum malaria in these provinces of Angola. Rapid parasite clearance and the absence of genetic evidence of artemisinin resistance are consistent with full susceptibility to artemisinin derivatives. Periodic monitoring of in vivo drug efficacy remains a priority routine activity for Angola. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12936-018-2290-9) contains supplementary material, which is available to authorized users.